1997
DOI: 10.1097/00006123-199707000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Bifrontal Craniectomy in the Treatment of Severe Refractory Posttraumatic Cerebral Edema

Abstract: Decompressive bifrontal craniectomy provides a statistical advantage over medical treatment of intractable posttraumatic cerebral hypertension and should be considered in the management of malignant posttraumatic cerebral swelling. If the operation can be accomplished before the ICP value exceeds 40 torr for a sustained period and within 48 hours of the time of injury, the potential to influence outcome is greatest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
307
1
19

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 488 publications
(342 citation statements)
references
References 12 publications
15
307
1
19
Order By: Relevance
“…In this series, there were no beds in the ICU for 24 patients (27%) after surgery, and they remained in the post-anesthesia recovery room, without ICP monitoring. But of all these factors, the only one that was statistically related (p<0.05) to bad prognosis was GCS upon admittance, in agreement with other authors 3,4,11,14 .It is worth emphasizing characteristics of the hospital where the study was carried out (Hospital Pronto Socorro João XXIII), which is a reference center for trauma in Minas Gerais. Although is has a large number of ICU beds, there is always a larger number of patients in the polytrauma room.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this series, there were no beds in the ICU for 24 patients (27%) after surgery, and they remained in the post-anesthesia recovery room, without ICP monitoring. But of all these factors, the only one that was statistically related (p<0.05) to bad prognosis was GCS upon admittance, in agreement with other authors 3,4,11,14 .It is worth emphasizing characteristics of the hospital where the study was carried out (Hospital Pronto Socorro João XXIII), which is a reference center for trauma in Minas Gerais. Although is has a large number of ICU beds, there is always a larger number of patients in the polytrauma room.…”
Section: Discussionsupporting
confidence: 85%
“…Among infection cases, four were meningitis, and the others were superficial. Polin et al reported 28.5% of hydrocephalus 11 . Guerra et al found subdural effusions in 26%, hydrocephalus in 14%, and infection in 2% 4 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Once the decision has been made to perform a decompressive craniectomy, Polin et al suggest doing so within 48 h of injury onset and report an advantage among pediatric patients when compared to matched controls taken from the Trauma Coma Data Bank [9]. Additionally, Aarabi et al found that patients with an admission GCS greater than 6 make them good candidates for decompressive craniectomy [10].…”
mentioning
confidence: 99%